‘My Sejahtera’ Application as COVID-19 Control Mechanism from Islamic Thought Perspective: Malaysia Experience - Mohd Khambali @ Hambali, Khadijah; Abdul Khalil, Shahidra; Daud, Mohd Zaidi (Afkar: Jurnal Akidah dan Pemikiran Islam, 2022)
The word ‘sejahtera’ or in English known as well-being or prosperity is widely used in Nusantara as a fundamental concept of human existence which is usually applied to various dimensions of life: physical, spiritual, intellectual, emotional, economic, political, governance, educational, social, cultural and religious. Furthermore, the Malay concept of ‘sejahtera’ has received wide attention from our community during this pandemic COVID-19 to ensure communities health. It is an important concept that deals with the issue of quality of life, society and civilisation as well. Given its importance, nurturing, and sustaining of a humane, peaceful, balanced and prosperous civilisation in this period of heightened global crises, in which most of mankind are currently starving for ‘sejahtera’ and struggling against an unprecedented COVID-19 pandemic, the Malay concept of ‘sejahtera’ will be reviewed from an Islamic thought perspective to build an alternative paradigm of holistic and sustainable development from the worldview of Tawḥīd. The study found that the Malaysian government’s MySejahtera programme, which uses a digital platform to serve as a one-stop shop, can help in a way to prevent the spread of COVID-19 in line with national law in achieving Maqāṣid al-Sharī‘ah.